The dipolar origin of protein relaxation - Hendrickx, H. (1968)
1. A set of parameters is proposed to check the interpretation of the dielectric behaviour of protein solutions as a rigid-dipole relaxation of prolate ellipsoids of revolution in the frequency range between 20 kHz and 10 MHz. Besides the δ(b)-function of Scheraga, another analogous function (δ(a)) is presented to establish size and shape of globular proteins. A study of the influence of solvent viscosity on the dielectric dispersion also gives strong evidence in favour of rigid-dipole relaxation. 2. Measurements of the dielectric dispersion of monomer solutions of bovine serum albumin and transferrin are reported. Monomers of bovine serum albumin were obtained by fractionation on Sephadex G-150. Low-conductivity solutions of both proteins are obtained by passage through an ion-exchange resin. 3. Computer analysis of the experimental dispersion curves by use of a two-term Debye dispersion gives valuable information about transferrin and leads to an axial ratio 4·5 for a prolate ellipsoid of revolution. The dielectric increment of bovine serum albumin is very low and no conclusive results have yet been obtained.